Genomic analysis for preweaning calf mortality in Nellore cattle - Garzón, Natalia Andrea Marín (2019)
Preweaning calf mortality is one of main causes of economic losses in beef cattle, since most of economic incomes are represented by the number of weaned calves available for sale. It is also detrimental for genetic progress due to the reduction of young candidates for selection. The inclusion of molecular markers in genetic analysis allows a better understanding of genetic mechanisms underlying calf mortality. The objectives of this study were: i) to estimate direct and maternal heritability of preweaning calf mortality in Nellore cattle and ii) to seek for genomic regions and candidate genes affecting direct and maternal effects of preweaning calf mortality in Nellore cattle. Variance components were estimated via Bayesian Inference using a threshold animal model, that included the systematic effects of contemporary group, birth weight as linear covariate, and age of dam at calving as linear and quadratic covariates. The direct and maternal genetics, and the residual were fitted as random effects. The final dataset used contained phenotypic records on 67,196 animals, offspring of 1,469 sires and 30,970 dams. The SNPs effects were estimated based on the weighted single-step GBLUP approach, using information of 8,443 genotyped animals with 410,936 SNPs. Direct and maternal heritability estimates were of 0.2143±0.0348 and 0.0137±0.0066, respectively. The top 10 genomic regions accounted for 13.61 and 14.23% of direct and maternal additive genetic variance and harbored a total of 63 and 48 positional candidate genes, respectively. Two overlapping regions located on BTA2 were identified, harboring common candidate genes for direct and maternal effects. The candidate genes RUNX3, CLIC4 and RCAN3, present into these regions, are involved in apoptotic pathway, signaling transducing, response to stimulus and immunological system. The genes CD53, LAMTOR5, ARF6, STPG1, CTNNA2, RALYL, CDKL1, and PROK1, were identified as candidates for direct effects of preweaning mortality as they are involved in cell regulation, preservation and survival. The genes CRADD and MAP3K5 were associated with maternal effects. These genes are involved in apoptosis, an important pathway for the normal development of pregnancy. These physiological roles may control genetic mechanism underlying preweaning calf mortality.